THE EFFECT OF FOREIGN DEBT, FOREIGN INVESTMENT (FDI), AND GOVERNMENT SPENDING ON ECONOMIC GROWTH IN 5 ASEAN COUNTRIES - Asnawi Asnawi; Padhil Hasyim; Khairil Anwar; Muhammad Roni (LPPM Universitas Malikussaleh, 2023)
This study aims to analyze the effect of foreign debt, foreign investment and Government spending on Economic Growth in 5 Asean Countries. The data used in this study is cross-sectiaon data from 2011-2020 obtained from the World Bank. The data is then analyzed using the Panel data regression model. The results of this study show that foreign debt has a positive and significant effect on economic growth in 5 asean countries. Foreign investment has no positive and significant effect. And Government spending has a positive and significant effect on economic growth in 5 Asean countries. The government is advised to carefully manage foreign debt to create positive Economic Growth, Create a conducive Investment climate and increase spending to boost Economic Growth.